Study on the Management of Maintenance and Marketing of Kampung Chickens at Alisa Farm, Alebo Village, Konda District - Utari, Komang Karisma; Sani, La Ode Arsad; Hadini, Hairil A; Munadi, La Ode Muh. (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
This study aims to determine the profile of the farming business, the maintenance of Kampung chickens, and the marketing of Kampung chickens at Alisa Farm. The study was conducted from May to June 2023, located at the Alisa Farm Kampung chicken business in Alebo Village, Konda District, South Konawe Regency. The research location was determined purposively (purposive sampling), and the respondents in this study were the owners of the Alisa Farm Kampung chicken business in Alebo Village, Konda District. The data analysis used in this study is descriptive qualitative analysis and marketing margin analysis. The research variables observed include the technical management of Kampung chicken maintenance, the marketing chain, and the marketing margin. The results of the study on Kampung chicken maintenance show that the maintenance system at Alisa Farm uses an intensive system, while the marketing results indicate that the marketing chain in the Alisa Farm Kampung chicken business consists of: Chain I: Farmer => End Consumer; and Chain II: Farmer => Retailer => End Consumer. The marketing margin in Chain II is IDR 10,000 per chicken, while there is no marketing margin in Chain I because no marketing institutions are involved.